Analisis Kerusakan Liner Pada Mud Pump Ideco T-800 Type Triplex Pump Berdasarkan Reliability, Availability, Dan Metode Fault Tree Analysis Di Pt. X - Aldi, Jupri; Yohanes, Yohanes; Yuhelson, Yuhelson (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Mud pump is one type of pump is widely used in industry, mud pump included in the positive type pump. Components of these machines often damage by suddenly one of them is theliner. The purpose of this study is to identify the critical component liner, evaluate the damage cause liner by the method of fault tree analysis (FTA), determine the basic design of the treatment and determine the optimum schedule component replacement liner, analyze the value of reliability, availability, mean time between failure (MTBF), mean time to repaire (MTTR). The existence of the effort are intended to increase the reliability and availability that high to maximize the life of the equipment, as well as the maintenance of an effective. Conclusions obtained includes critical component is the liner 1, cause damage to the liner is scratch. The processing data using Minitab software 16 to determine distribution test, thevalue of MTTR, MTBF, reliability and availability. It is obtained the optimal schedule component liner replacements is done every 56 day with some advantages namely the frequency of replacement of the liner component decreased from an average of 11 times/year be 7 times/year and an increase in the value of reliability in the liner 2.Keywords : Mud Pump, Liner, Reliability, Availability, FTA